Menstrual Toxic Shock Syndrome: A French Nationwide Multicenter Retrospective Study. (27th April 2021) - Contou, Damien; Colin, Gwenhaël; Travert, Brendan; Jochmans, Sébastien; Conrad, Marie; Lascarrou, Jean-Baptiste; Painvin, Benoit; Ferré, Alexis; Schnell, David; La Combe, Beatrice; Coudroy, Rémi; Ehrmann, Stephan; et al.
Abstract: Background: Studies describing the clinical features and short-term prognosis of patients admitted to the intensive care unit (ICU) for menstrual toxic shock syndrome (m-TSS) are lacking. Methods: This was a multicenter retrospective cohort study of patients with a clinical diagnosis of m-TSS admitted between 1 January 2005 and 31 December 2020 in 43 French pediatric (n = 7) or adult (n = 36) ICUs. The aim of the study was to describe the clinical features and short-term prognosis, as well as to assess the 2011 Centers for Disease and Control (CDC) diagnostic criteria, in critically ill patients with m-TSS. Results: In total, 102 patients with m-TSS (median age, 18 years; interquartile range, 16–24 years) were admitted to 1 of the participating ICUs. All blood cultures (n = 102) were sterile. Methicillin-sensitive Staphylococcus aureus grew from 92 of 96 vaginal samples. Screening for superantigenic toxin gene sequences was performed for 76 of the 92 vaginal samples positive for S. aureus (83%), and toxic shock syndrome toxin 1 was isolated from 66 strains (87%). At ICU admission, no patient met the 2011 CDC criteria for confirmed m-TSS, and only 53 (52%) fulfilled the criteria for probable m-TSS. Eighty-one patients (79%) were treated with antitoxin antibiotic therapy, and 8 (8%) received intravenous immunoglobulins. Eighty-six (84%) patients required vasopressors, and 21 (21%) tracheal intubation. No patient required limb amputation or died in the ICU. Conclusions: In this large multicenter series of patients included in ICUs for m-TSS, none died or required limb amputation. The CDC criteria should not be used for the clinical diagnosis of m-TSS at ICU admission. Abstract : None of the patients with menstrual toxic shock syndrome required limb amputation or died despite a high rate of vasopressor support and invasive mechanical ventilation. Centers for Disease Control and Prevention criteria should not be used for clinical diagnosis at intensive care unit admission.